ChemInform Abstract: Oxidative Allylic Esterification of Alkenes by Cooperative Selenium‐Catalysis Using Air as the Sole Oxidant. Issue 44 (13th October 2016) - Ortgies, Stefan; Depken, Christian; Breder, Alexander
Abstract: The novel oxidative coupling of nonactivated alkenes with simple carboxylic acids proceeds with excellent regioselectivity as well as good functional group tolerance.